The Role of Indonesian Cultural Diplomacy for Fiji in The Agenda "Harmony For The Pacific" - Ross Mochammad Alifano; Try Danu Wijaya; Agfajrina Cindra Pamungkas (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
This study analyzes Indonesia’s cultural diplomacy toward Fiji through the Harmony for the Pacific initiative within the Indo-Pacific bilateral framework. The Indo-Pacific is strategically important for Indonesia due to its geopolitical significance and historical-cultural ties with Melanesian countries, including Fiji. Shared cultural heritage and common developmental experiences provide a strong foundation for soft power-based relations. Using a qualitative descriptive method grounded in Multitrack Diplomacy In the Harmony for the Pacific program, elements of Indonesian literature are indirectly present through oral literature and visual narratives. Program participants not only engage in performing arts but also learn the "storytelling style" of the local community in Labuan Bajo, which reflects the rich narrative traditions of the archipelago. Furthermore, the screening of the film "ORPA," which tells the story of a Papuan girl's struggle, demonstrates how visual narrative functions as a modern literary medium to convey Indonesian humanitarian and cultural values, particularly from the eastern region, which has ethnographic connections and cultural diplomacy theory, the study finds that Harmony for the Pacific has strengthened Indonesia–Fiji relations by enhancing people-to-people engagement, cross-cultural understanding, and Indonesia’s positive image in the Pacific. The program has also generated spillover effects, particularly in economic and educational cooperation, highlighting cultural diplomacy as an effective instrument of Indonesia’s foreign policy in the Pacific region.